PENGARUH HEALTH EDUCATION TERHADAP PENGETAHUAN DAN SIKAP WANITA DEWASA TENTANG “ SADARI “ DALAM UPAYA DETEKSI DINI Ca MAMMAE DI KEDIRI - Byba Melda Suhita (STRADA : Jurnal Ilmiah Kesehatan, 2012)
Breast cancer became improve when found in early stadium, usually in small size. The Early effort was Breast Self Examination (BSE). The Population was all adult women in Kediri, using Accidental sampling, to get 99 persons of population as sample. The Analysis was use t-test and Regresi. The result analysis of knowledge differentiation about BSE in the effort of breast cancer early detection gotten -5,706 t score with 0,000 P-Value less then α (0,05), its mean there was differentiation between knowledge of adult women before and after health education. The Mean different shown negative value (-1,1919) its mean the knowledge before less then after health education about BSE has positive effect on knowledge. The result analysis of attitude differentiation about BSE in the effort of breast cancer early detection gotten -6,418 t score with 0,00 P-Value less then α (0,05), its mean there was differentiation between attitude of adult women before and after health education. The Mean different shown negative value (-1,1919) its mean the attitude before less then after health education about BSE, that showing positive effect on attitude.The Regression analysis shown F value amount 16,321 with P Value 0,00 less then α (0,05), its mean H0 refused and H1 accepeted, its shown that there was health education effect on knowledge and attitude improvement in BSE as effort of breast cancer early detection in Kediri. Improvement of knowledge and attitude on BSE as effort of breast cancer early detection in Kediri could done by health education.